High cross-plane thermally conductive hierarchical composite using graphene-coated vertically aligned carbon nanotubes/graphite. (August 2019) - Lv, Feng; Qin, Mengmeng; Zhang, Fei; Yu, Huitao; Gao, Long; Lv, Peng; Wei, Wei; Feng, Yiyu; Feng, Wei
Abstract: Thermally conductive carbon-based composites in the cross-plane direction is of significant importance for efficient heat dissipation. Fabricating one-dimensional (1D) ordered structure at the interlayer of graphite (GT) effectively improves its cross-plane thermal conductivity ( k ⊥ ). However, this structure deteriorates during subsequent hot-pressing owing to its low structural stability. Herein we report a three-dimensional (3D) graphene-coated vertically aligned carbon nanotubes (VACNTs)/graphite (GT) composite with high k ⊥ value. A uniform coating of reduced graphene oxide (rGO) on VANCTs results in efficient heat conduction throughout the large-area, bendable nanosheets and forms ordered arrays in the cross-plane direction owing to the high structural integrity. The thermal conductivity of the graphite-based blocks prepared by hot-pressing can be controlled via combined effects of the length of the VACNTs used for the two-dimensional (2D) coating and uniformity of the rGO coating. With a relatively low density (1.67 g/cm 3 ), the rGO-VACNTs/GT composite exhibits a maximum k ⊥ value of 32.96 W/m·K, 60% higher than VACNTs/GT (20.1 W/m·K; density = 1.85 g/cm 3 ). Laser-induced thermochromic patterns confirm that the rGO-VACNTs/GT composite exhibits excellent heat conduction. Thus, 2D-coated/1D array assemblies can be developed for advanced high-strength and thermally-conductive materials by optimizing their hierarchical microstructure. Graphical abstract: Image 1